Dampak Kegiatan Keagamaan Rohis melalui Kajian Kitab Kuning bagi Akhlak Peserta Didik - Ahmad Burhanudin (Jurnal Hikmatuna, 2019)
Instilling and fostering morals is very important, and formal institutions such as schools have an obligation to recite morals early on to students. Ideally, schools provide two programs in the process of moral formation, namely intraculicular and extracurricular. Rohis religious program is one of the best solutions offered. This type of research is field research with a qualitative descriptive approach. The purpose of this research was to find out about how planing, the implementation, the evaluation and the supporting factors of this yellow book program. After that, identify the impact of this yellow book study on the morals of students. This research resulted that the planning, implementation and evaluation processes had proceeded as expected. It even has a positive impact on the morals of students, because it can indirectly add insight and knowledge of students related to moral material, more than that students become more understanding about something that must be done and also avoided. For example 1) students respect the teacher more, such as greeting and kissing the teacher's hand. 2) there are no more truant students, both at school and at school hours.